Lactobacillus paracasei Reduces Intestinal Inflammation in Adoptive Transfer Mouse Model of Experimental Colitis. (13th June 2011) - Oliveira, Manuel; Bosco, Nabil; Perruisseau, Genevieve; Nicolas, Jeanne; Segura-Roggero, Iris; Duboux, Stéphane; Briand, Muriel; Blum, Stéphanie; Benyacoub, Jalil
Abstract : Studies showed that specific probiotics provide therapeutic benefits in inflammatory bowel disease. In vitro evidence suggested that Lactobacillus paracasei also called ST11 (CNCM I-2116) is a potent strain with immune modulation properties. However, little is known about its capacity to alleviate inflammatory symptoms in vivo In this context, the main objective of this study was to investigate the role of ST11 on intestinal inflammation using the adoptive transfer mouse model of experimental colitis. Rag2 -/- recipient mice were fed with ST11 (10 9 CFU/day)a month prior toinduce colitis by adoptive transfer of naive T cells. One month later, in clear contrast to nonfed mice, weight loss was significantly reduced by 50% in ST11-fed mice. Further analysis of colon specimens revealed a significant reduction neutrophil infiltration and mucosal expression of IL1 β, IL-6, and IL12 proinflammatory cytokines, whereas no consistent differences in expression of antibacterial peptides or tight junction proteins were observed between PBS and ST11-fed mice. All together, our results demonstrate that oral administration of ST11 was safe and had a significant preventive effect on colitis. We conclude that probiotics such as Lactobacillus paracasei harbor worthwhile in vivo immunomodulatory properties to prevent intestinal inflammation by nutritional approaches.